The Food Doctor Diet - Marber, Ian (Dorling Kindersley Ltd, 2003)
Combining accessible, contemporary design with mouth-watering recipes to create a sophisticated look for jaded palates, The Food Doctor Diet provides a realistic and enjoyable plan that is safe, practical and achievable. This seven-day menu program--without deprivation, yo-yo dieting, or portion control--is the diet to follow when all others fail. Written by a respected dietitian, this book debunks the myths and offers a safe, sensible alternative to the fads and hype of most diets.
Keywords: Cooking; Health and Healing; Non-Fiction